A Small Amount of Sn Addition Effect to Cu-15Zn Alloy on Structure, Microstructure, Hardness, Corrosion Resistance, and Antibacterial Activity - Basori, Imam; Sari, Yunita; Prasetya, Dendy Wardhana; Susetyo, Ferry Budhi; Alias, Juliawati; Budi, Setia; Yudanto, Sigit Dwi; Hasbi, Muhammad Yunan; Situmorang, Evi Ulina Margareta; Edbert, Daniel (Science and Technology Indonesia, 2025)
Cu-15Zn alloy is widely used as a heat exchanger pipe. CuZn alloy was also used for cardiovascular implant applications. Several problems have been found in that alloy, such as less corrosion resistance. Therefore, various Sn (0.2, 0.7, 1, and 2 wt.%) were added to Cu-15Zn alloy in the present research to enhance corrosion resistance. Afterwards, the alloy was homogenized at 800 °C for 2 hours. Several investigations were conducted, such as structure, microstructure, hardness, corrosion resistance, and bacterial activity, using XRD, Optical microscope, Vickers hardness, Potentiostat equipment, and Digital camera. More Sn content leads to an increase in volume and a decrease in hardness. Presenting Sn in the alloy does not influence the phase in the alloy microstructure. The highest Sn content in the alloy promoted a more positive value of the alloy, indicating that the sample is more cathodic, probably due to the protective layer on the surface. A concentration of 1 wt.% Sn exhibits the most effective antibacterial effect probably due to the small crystallite size.